An approach to indirect costs of disability in Colombia (2005)
OBJECTIVES: This document studies the relationships between economic policy and disability, representing an attempt at providing a theoretical analysis for economic policy of disability in Colombia. METHODS: The absolute figures and percentages of distribution of disability in the Colombian population from 1981 to 2003, obtained from 3 official sources, were used. The following variables were selected: age, education, employment, socio-economic level, income and dependence. Several hypotheses were formulated and contrasted with frequency analysis and the Chi-square test to estimate differences between groups. RESULTS: The analysis demonstrated that vulnerability to disability is different according to: 1. Sex, with a greater impact on males; 2. Age: greater impact for older age groups and, in the last 3 years, greatest impact in the 25 to 55 year age group under potential risk of disability; 3: Region: greater vulnerability in rural areas and 4. Socio-economic level: persons with disabling conditions belong to the lower socio-economic strata. The typical profile of persons with disabling conditions is poor education, income of less than a minimum monthly wage, unemployed, belonging to the 1 or 2 socio-economic strata, forming part of homes defined as poor, being male and living in rural areas. CONCLUSIONS: Poverty seems to enhance disability increasing vulnerability, risk and restricting opportunities for welfare. These results can be used as arguments for redirecting the policies and actions for greater access of disabled persons to social and economic opportunities.